Developing a process model for circular economy business model innovation within manufacturing companies. (25th May 2021) - Pieroni, Marina P.P.; McAloone, Tim C.; Pigosso, Daniela C.A.
Abstract: Circular Economy business model innovation is challenging, as it requires the consideration of new variables, adding complexity to decision-making. Despite the range of existing approaches for Circular Economy business model innovation, they are limited in providing adequate advice to practitioners. Key limitations are related to: lack of a holistic structure with systematisation of practices; focus on single innovation stages; lack of analytical and decision-support structures and; marginal consideration of institutional and strategic aspects, as well as interdependencies with other business processes. This paper addresses these limitations by developing a systematic process model for Circular Economy business model innovation, in close collaboration with seven manufacturing companies. The process model contains four stages (prepare, sense, seize and transform) with recommendations of institutional, strategic and operational practices (including activities, tools, interdependencies, decision gates, and recommended mindset and attitudes). The process model brings unique contributions to manufacturing companies by providing: (i) a systematic structure to strengthen and mature existing Circular Economy business model ideas into viable and implementable concepts, and (ii) a source of inspiration for best practice Circular Economy business models in specific sectors. Furthermore, the paper contributes to the body of knowledge that develops Circular Economy methodology by (i) consolidating a holistic and systematic view of practices for Circular Economy business model innovation within manufacturing companies, and; (ii) providing an example of approach to develop methodological support that is able to offer proactive advice to practitioners.